2000
DOI: 10.1074/jbc.m001629200
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of Reactive Oxygen Species as Intracellular Mediators of Hyperthermia-induced Apoptosis

Abstract: The effects of cellular antioxidant capacity on hyperthermia (HT)-induced apoptosis and production of antiapoptotic heat shock proteins (HSPs) were investigated in HL-60 cells and in HL-60AR cells that are characterized by an elevated endogenous catalase activity. Exposure of both cell lines to 43°C for 1 h initiated apoptosis. Apoptosis peaked at 3-6 h after heat exposure in the HL-60 cells. Whereas HL-60AR cells were partially protected against HT-induced apoptosis at these early time points, maximal levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 34 publications
6
86
0
Order By: Relevance
“…In this respect, it has been demonstrated that in large tumor spheroids overexpressing P-glycoprotein low levels of ROS downregulated P-glycoprotein, whereas in small tumor spheroids, which are devoid of an MDR phenotype, oxidative stress induced upregulation of P-glycoprotein. 16,17 Heat incubation-induced oxidative stress has been recently reported for human T lymphocytes, 51 rat cardiomyocytes, 52 BC-8 macrophages 36, PC-3 prostate cancer cells 53 and HL-60 cells 24 ; however the source of ROS has not yet been identified. In our study hyperthermia treatment of tumor spheroids resulted in a robust increase of ROS presumably through the activity of an NADPH-oxidase, which has recently been demonstrated by us to be highly expressed in small tumor spheroids but downregulated with the induction of cell quiescence and MDR in large tumor spheroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, it has been demonstrated that in large tumor spheroids overexpressing P-glycoprotein low levels of ROS downregulated P-glycoprotein, whereas in small tumor spheroids, which are devoid of an MDR phenotype, oxidative stress induced upregulation of P-glycoprotein. 16,17 Heat incubation-induced oxidative stress has been recently reported for human T lymphocytes, 51 rat cardiomyocytes, 52 BC-8 macrophages 36, PC-3 prostate cancer cells 53 and HL-60 cells 24 ; however the source of ROS has not yet been identified. In our study hyperthermia treatment of tumor spheroids resulted in a robust increase of ROS presumably through the activity of an NADPH-oxidase, which has recently been demonstrated by us to be highly expressed in small tumor spheroids but downregulated with the induction of cell quiescence and MDR in large tumor spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Hyperthermia-induced upregulation of P-glycoprotein may be associated to an elevation of intracellular ROS levels. Indeed it has been recently shown that hyperthermia increases generation of ROS in HL-60 cells 24 as well as in mice, 25 and it has been suggested that hyperthermia-induced ROS may play a role as signaling molecules that transduce the stress signal to the cell nucleus. Within the signaling cascade hyperthermia 26 as well as ROS 27 have been shown in a number of studies to activate MAPKs including ERK1,2, JNK, and p38.…”
mentioning
confidence: 99%
“…Although controversial, ROS have been implicated as common mediators of apoptosis in a variety of cells, including neutrophils (15,37,38). In the present study, we used DPI, a flavoprotein inhibitor of NADPH oxidase (33), to address the possibility that ROS are involved in Mtb-induced apoptosis in neutrophils.…”
Section: Tuberculosis-induced Apoptosis In Neutrophils Via An Oxygmentioning
confidence: 99%
“…Unfortunately, the biological processes underlying resistance remain unknown. Hyperthermia improves the effectiveness of chemotherapy by creating oxygen free radicals, which activate signaling pathways leading to cell death, by oxidizing DNA, membrane lipids, and proteins (Katschinski et al 2000;Wang et al 2007).…”
Section: Discussionmentioning
confidence: 99%